Turbulent Free Convection and Thermal Radiation in an Air-Filled Cabinet with Partition on the Bottom Wall - Igor V. Miroshnichenko; Mikhail A. Sheremet (Axioms, 2023)
Computational analysis is performed for turbulent free convection and surface thermal radiation in an air-filled cavity with solid obstacle on the bottom wall. A partition of finite thickness is considered, the position, length, and heat conductivity of which vary for certain values of the Rayleigh number. The coupled heat transmission by thermal radiation, free convection and heat conduction through the solid obstacle and walls is studied. The governing equations are solved by the finite difference method. This work also contains a detailed description of the computational grid thickening procedure. Temperature patterns and airflow field are scrutinized for some specific conditions using streamlines and isotherms. The overall heat transfer within the cavity is analyzed in terms of the mean convective and radiative Nusselt numbers, and many of the data are presented in detail for various partition positions, heat conductivities of the partition and walls of the cavity, and Rayleigh numbers. The results report that the participation of partitions within the cavities in the heat exchange processes decreases the overall heat transfer rate compared to the simpler case of cavities without partitions.